The Effects of Exogenous Administration of Human Coagulation Factors Following Pig‐to‐Baboon Liver Xenotransplantation. Issue 6 (5th February 2016) - Navarro‐Alvarez, N.; Shah, J. A.; Zhu, A.; Ligocka, J.; Yeh, H.; Elias, N.; Rosales, I.; Colvin, R.; Cosimi, A. B.; Markmann, J. F.; Hertl, M.; Sachs, D. H.; et al.
Abstract : We sought to determine the effects of exogenous administration of human coagulation factors following pig‐to‐baboon liver xenotransplantation (LXT) using GalT‐KO swine donors. After LXT, baboons received no coagulation factors (historical control, n = 1), bolus administration of a human prothrombin concentrate complex (hPCC; 2.5 mL/kg, n = 2), continuous infusion of hPCC (1.0 mL/h, n = 1) or continuous infusion of human recombinant factor VIIa (1 µg/kg per hour, n = 3). The historical control recipient demonstrated persistent thrombocytopenia despite platelet administration after transplant, along with widespread thrombotic microangiopathy (TMA). In contrast, platelet levels were maintained in bolus hPCC recipients; however, these animals quickly developed large‐vessel thrombosis and TMA, leading to graft failure with shortened survival. Recipients of continuous coagulation factor administration experienced either stabilization or an increase in their circulating platelets with escalating doses. Furthermore, transfusion requirements were decreased, and hepatic TMA was noticeably absent in recipients of continuous coagulation factor infusions compared with the historical control and bolus hPCC recipients. This effect was most profound with a continuous, escalating dose of factor VIIa. Further studies are warranted because this regimen may allow for prolonged survival following LXT. Abstract : The authors investigate a novel approach of administering exogenous human coagulation factor following pig‐to‐baboon liver xenotransplantation, which appears to maintain circulating platelets, limit transfusion requirements, and prevent thrombotic microangiopathy. See the related brief communication from Buhler et al onpage 1917 .